PENGEMBANGAN MODUL AJAR KELAS IV TERINTEGRASI AL-QUR’AN DAN HADIS TEMA 7 DI SD IP DAARUTH THULLAB - M. Anggrayni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The background of this research is learning on theme 7 about How Beautiful Diversity is in My Country which is contained in the thematic books that have not yet integrated the Al-Qur'an and Hadith, therefore SD IP Daaruth Thullab really needs teaching materials that integrate the Qur'an and Hadith. To overcome this, researchers are trying to develop teaching materials in the form of class IV modules integrated with the Qur'an and Hadith which aim to help teachers and students gain new insights and add teaching materials that integrate the Qur'an and Hadith at SD IP Daaruth Thullab which are valid, practical and effective, so as to improve student learning outcomes at SD IP Daaruth Thullab.The type of research is develepment research, which uses the ADDIE model whic consists of Analyze, Design, Development, Implementation, and Evaluation. The test subjects are foruth grade students of SD IP Daaruth Thullab. The research instrument was in the form a validation sheet, practicality and effectiveness. This assesment instrument is validated by three validators, content validator, construct validator and languagevalidator, then the module practicality sheet is determined by the practitioner. And the effectiveness of the module is determined from the learning outcomes of fourth grade students at SD IP Daaruth Thullab.The results of the validation assessment of the integrated class IV module of the Qur'an and Hadith on the validation test by three experts had an average score of 84.52% with a very valid category. The results of practicality by grade IV teachers with an average result of 96% with a very practical category. The results of the effectiveness of the module carried out by students with an average of 92.30% are categorized as very effective.